2015
DOI: 10.1177/0958928715594544
|View full text |Cite
|
Sign up to set email alerts
|

The end of the honeymoon: The increasing differentiation of (long-term) unemployment risks in Europe

Abstract: This article discusses the changing social distribution of unemployment and long-term unemployment risks during the current financial and economic crisis. These risks are interpreted as the result of three different, overlapping forms of labour market segmentation: first, the institutionally stabilized polarization between labour market insiders and outsiders; second, the occupational dualization of high- and low-skilled employees and occupations; and third, the marginalization of disadvantaged social groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(50 reference statements)
1
12
0
2
Order By: Relevance
“…Nevertheless, rising risks of low wages are strongly skill-biased: high-skilled occupations are partly exempt from the otherwise universal trend. This is consistent with a growing body of research that shows increasing labour market disparities by skill levels (Abrassart, 2015;Gebel and Giesecke, 2011;Giesecke and Heisig, 2010;Heidenreich, 2015). In addition, we also reveal a pattern of polarization between full-time and part-time employed households, as low-wage risks among the latter increased disproportionately.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, rising risks of low wages are strongly skill-biased: high-skilled occupations are partly exempt from the otherwise universal trend. This is consistent with a growing body of research that shows increasing labour market disparities by skill levels (Abrassart, 2015;Gebel and Giesecke, 2011;Giesecke and Heisig, 2010;Heidenreich, 2015). In addition, we also reveal a pattern of polarization between full-time and part-time employed households, as low-wage risks among the latter increased disproportionately.…”
Section: Discussionsupporting
confidence: 90%
“…We add to our previous knowledge in two respects. First, by putting the trends in job quality in the context of labour market cleavages by employment position and sector beyond and above growing skill-divides in the labour market with respect to wages, poverty and employment risks (Abrassart, 2015;Dustmann et al, 2009;Heidenreich, 2015;Kalleberg, 2011;Rovny, 2014). Second, we will study the changing relationship between two aspects of job quality -low wages and low working hoursand its implications for in-work poverty risks.…”
Section: Introductionmentioning
confidence: 99%
“…While the economic and financial crisis has reinforced the occupational and social dualization of labour markets (Heidenreich, 2015; more generally on the crisis, Dunlop and Radaelli, 2016; Tosun et al, 2014), it has also provided an opportunity to address the issue of youth unemployment at the European level (Lahusen et al., 2013). Recognizing the potential gains both for individuals and societies overall, the European Parliament and the European Council decided in May 2014 that PES in the EU member states shall cooperate in an attempt to promote and share best practices (Hall et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The independent variables introduced in our model are as follows: Individual characteristics : age and gender. Both are closely linked to the likelihood of employment in a number of European countries (see, for example, Heidenreich, ). Family socioeconomic background Immigrant status : Previous studies have shown the relevance of place of birth as a determinant of labour market outcomes in European countries (Heath, Rothon, & Kilpi, ). Thus, we distinguished between natives, first generation immigrants, and second generation immigrants.…”
Section: Methodsmentioning
confidence: 99%
“…Individual characteristics: age and gender. Both are closely linked to the likelihood of employment in a number of European countries (see, for example, Heidenreich, 2015).…”
Section: Calero and Choi | 351mentioning
confidence: 99%